Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Google-Books-ID: CHE3DwAAQBAJ
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

Challenging the Myth of Gender Equality in Sweden - Lena, Martinsson; Gabriele, Griffin (Policy Press, 2016)
Sweden is often considered one of the most gender-equal countries in the world and held up as a model to follow, but the reality is more complex. This is the first book to explode the myth of Swedish gender equality, both offering a new perspective for an international audience, and suggesting how equality might be rethought more generally. While the authors argue that the gender-equality mantra in Sweden has led to a society with increased opportunities for some, they also assert that the dominant norm of gender equality has become nationalistic and builds upon heteronormative and racial principles. Examining the changing meanings and parameters of gender equality against the country's social-democratic tradition and in the light of contemporary neoliberal ideologies, the book constitutes an urgent contribution to the debates about gender-equality policies and politics.
Keywords: Social Science / Gender Studies; Social Science / Sociology / General

The Aftermath of Feminism: Gender, Culture and Social Change - McRobbie, Angela (SAGE Publications, 2009)
Congratulations to Dr. McRobbie! This book has been named to the list of books for the 2009 Critics Choice Book Award of the American Educational Studies Association (AESA).These essays show Angela McRobbie reflecting on a range of issues which have political consequence for women, particularly young women, in a context where it is frequently assumed that progress has been made in the last 30 years, and that with gender issues now 'mainstreamed' in cultural and social life, the moment of feminism per se is now passed. McRobbie trenchantly argues that it is precisely on these grounds that invidious forms of gender -re-stabilisation are able to be re-established. Consumer culture, she argues, encroaches on the terrain of so called female freedom, appears supportive of female success only to tie women into new post-feminist neurotic dependencies. These nine essays span a wide range of topics, including - the UK government's 'new sexual contract' to young women, - popular TV makeover programmes, - feminist theories of backlash and the 'undoing' of sexual politics, - feminism in a global frame- the 'illegible rage' underlying contemporary femininities.
Google-Books-ID: jmMREuksN10C
Keywords: Social Science / Essays; Social Science / Feminism & Feminist Theory; Social Science / Sociology / General; Social Science / Women's Studies